(untitled) (Research, Society and Development, 2021)
The medical course requires intellectual and emotional preparation. When entering the course, dedication, intense workload and countless hours of study are required, in addition to intense pressure. The aim of this study is to understand the academic environment and quality of life of basic cycle medical students at the University of Uberaba. This is a prospective quantitative study of a descriptive observational cross-sectional nature. Students from the basic cycle of the medical course at the University of Uberaba were selected by simple random probability sampling. The perception regarding the teaching environment was analyzed using the DREEM questionnaire. The quality of life of the students was evaluated by the WHOQOL-BREF questionnaire. The survey was answered by 218 (77.3%) students, 63.8% female and 36.2% male. The socioeconomic questionnaire showed that 60.6% of the students are between 16 and 20 years old, and 39.9% live with their parents. Only 13.8% receive psychological counseling. According to the DREEM questionnaire, the students’ perception was more positive in the learning, teachers, academic, atmosphere, and social domains. The WHOQOL-BREF questionnaire evaluated four domains. The physical domain had a mean of 3.43, psychological 21.31, social 3.79, and environmental 3.84. The perception of the students in relation to the academic environment was more positive than negative, but in need of improvement. The students’ quality of life was considered positive regarding the physical and environmental aspects, and pointed out as negative in the physical and psychological issues. More comprehensive studies could contribute to the improvement of interventions to improve the educational environment.